The Contributions of European Ships to the (Frankish) Crusades in the Period 1095 to 1248 - Al Hlalat, Fadia; Al Rwaidi, Mahmoud Mohammad (Jordan Journal for History and Archaeology, 2024)
Europe relied in its military equipment for the (Frankish) Crusades on fleets, to transport troops, equipment, military supplies, pilgrims, supplies, build bridges and carry wood across the seas, but the Europeans took the (Frankish) Crusades as a pretext to employ their ships in trading to achieve their economic interests to the religious and military side required of them, without taking any consideration to the dangers they face at sea. This is evidenced by the ships hired by the European kings, princes and leaders of the (Frankish) Crusades and employed them in the service of their (Frankish) Crusades on the Holy Land. European ships, especially Italian ones, took control; because of its design and crews trained on the sea, enduring the trouble of travel and their knowledge of the winds, the great role in the military support of the Latin (Frankish) Crusader outposts in the Holy Land and the Levant. The dependence of the Crusader forces on ships made a big difference in their success in the Holy Land in securing and fortifying the coastal cities that were in the possession of the (Frankish) Crusaders and turned them into centers for commercial ships, and spread a state of terror among the inhabitants of the coastal regions.